Exploring Social Constructivist Practices: Collaborative Learning Challenges and Strategies in TEFL Classrooms at Islamic Boarding Schools - Azizah, Rizki; Ulayya, Putri Itsna; Fauziati, Endang (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2025)
Islamic boarding schools play a vital role in Indonesia’s education system, particularly in shaping students’ religious and academic development. Within these institutions, implementing collaborative learning presents unique challenges due to their emphasis on discipline, religious values, and limited technological access. This study aims to explore Islamic boarding school teachers’ perspectives on the challenges of applying social constructivist approaches in collaborative learning within TEFL classrooms, as well as the strategies used to overcome these obstacles. Using a qualitative design, data were collected through semi-structured interviews with five teachers and analyzed using thematic analysis. The findings reveal that while collaborative learning can enhance students’ motivation, critical thinking, and language skills, it requires careful planning and ongoing professional development to be effective in this context. Challenges identified include curriculum constraints, school culture, inadequate facilities, diverse student cognitive abilities, varying motivation levels, and emotional regulation. The study underscores the importance of strategic lesson planning, effective group composition, and teacher training in addressing these issues and improving collaborative learning in Islamic boarding school settings.